Profil Perencanaan Karir Siswa Sekolah Menengah Kejuruan dengan Pemodelan Rasch Berdasarkan Jenis Kelamin - Rangka, Itsar Bolo; Prasetyaningtyas, Wahyu Eka; Satrianta, Hengki; Folastri, Sisca (Konselor, 2017)
This research aimed to (1) perform inventory career planning of students, and (2) measuring students career planning based on gender. Data analysis used Rasch model for 45 students with actual power measurement 0.9272652. The research findings showed (1) inventory career planning has been fit with the theoretic model, and (2) female student have a tendency to a higher career planning rather than male student. In the future, to measurement of student’s career planning by using this inventory can only produce a high measurement information for students who have a mediocre ability. Further, the researcher need to consider to eliminate item No. 12 in this inventory due to the biased towards the male gender.